2000
DOI: 10.1046/j.1524-475x.2000.00103.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone does not attenuate the inhibitory effects of sepsis on wound healing

Abstract: Chronic abdominal sepsis is associated with impaired tissue repair. Treatment of burn patients with growth hormone results in improved healing of skin graft donor sites. The goal of this study was to determine whether administration of growth hormone could attenuate the inhibitory effects of sepsis on cutaneous wound healing. Four groups of male Sprague Dawley rats were studied: control, control + growth hormone, sepsis, and sepsis + growth hormone. Sepsis was caused by implantation of a bacterial focus in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…In this review, 43 of the 55 studies were identified that had wounds placed on the dorsum of the rats 6,9–13,18–54 . There was an overlap in categorizing the groups according to wound placement because wounds were made in different areas within the same study; for example, wounds were made on the dorsum and the ventral portion of rats 53 . Exact statements as to locations and depths of wounds were not always readily available, leaving the reader to draw assumptions from both the text and figures 55 .…”
Section: Wound Locationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this review, 43 of the 55 studies were identified that had wounds placed on the dorsum of the rats 6,9–13,18–54 . There was an overlap in categorizing the groups according to wound placement because wounds were made in different areas within the same study; for example, wounds were made on the dorsum and the ventral portion of rats 53 . Exact statements as to locations and depths of wounds were not always readily available, leaving the reader to draw assumptions from both the text and figures 55 .…”
Section: Wound Locationmentioning
confidence: 99%
“…Details on the research animals are included in Table 4. Thirty‐one of the 55 studies used the Sprague‐Dawley strain of rat 5,6,9–13,15,19–22,24,26,28,31–33,36,37,40,44,46,48,51,53,59, 60,68–70 . The second most popular was the Wistar strain with 15 studies 14,16,17,25,27,29,30,34,39,41,43,49,50,52,55 .…”
Section: Strain and Sex Of Ratsmentioning
confidence: 99%
“…However, the effects of GH on collagen formation are probably tissue‐specific. GH treatment in rats did not increase collagen deposition in cutaneous wounds 31 . Hypertrophic scars have not been reported in acromegaly patients, whose condition is characterized by overproduction of GH.…”
Section: Discussionmentioning
confidence: 72%
“…The effect of GH on wound healing in sepsis was controversial [27][28][29][30]. Stamm et al [10] had found that breaking strength of incisional wounds and hydroxyproline content were reduced in septic rats, administration of GH for 5 days did not improve breaking strength or collagen deposition in septic animals, so the investigators believed that GH is unlikely to improve tissue repair in sepsis-induced catabolic illness. In this study, we found that administration of rhGH for 5 days fail to improve intestinal healing in intra-abdominal sepsis, the combination of FG and rhGH have no advantage over using FG alone in improving intestinal healing.…”
Section: Discussionmentioning
confidence: 99%
“…Stamm and his colleagues, however, had demonstrated that the administration of GH for 5 days did not improve collagen deposition or breaking strength in cutaneous wounds in septic rats [10]. The effect of GH on intestinal anastomotic healing in intra-abdominal sepsis has not been known.…”
Section: Introductionmentioning
confidence: 99%